Watching the clock: Challenges for the world's fastest growing economies - Knowledge@SMU (Institutional Knowledge at Singapore Management University, 2011)
Time seems to move a little faster in economies with greater wealth, higher education and more demanding jobs; sometimes driven by personal ambitions to achieve more, or perhaps because society demands it. Speaking at a Wee Kim Wee Centre Lunchtime Seminar, renowned China expert Wang Gungwu says that life on the fast lane has become so ingrained in our thinking of modern societies that it is no longer questioned but accepted as a condition of development: Speed up or get left behind.